1996
DOI: 10.1037/0894-4105.10.4.495
|View full text |Cite
|
Sign up to set email alerts
|

Verb confrontation naming and word-picture matching in Alzheimer's disease.

Abstract: Patients with Alzheimer's disease (AD) were asked to name pictures and perform a multiplechoice word-picture matching task with verbs and nouns. AD patients were significantly more impaired with verbs than nouns for both naming and word-picture matching, and their patterns of semantic naming errors differed for verbs and nouns. One subgroup of AD patients was compromised on both naming and word-picture matching consistent with a semantic memory deficit. Naming was worse for verbs than for nouns in these patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

5
33
0
2

Year Published

1998
1998
2007
2007

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 33 publications
(40 citation statements)
references
References 52 publications
(81 reference statements)
5
33
0
2
Order By: Relevance
“…One factor concerns the increased resource demands that may be associated with processing all of the knowledge represented in a verb. Although difficulty with verb confrontation naming and verb-picture matching do not correlate with executive resource deficits in AD White-Devine et al, 1996), we cannot rule out that the need to maintain a rich corpus of semantic, thematic, and grammatical knowledge in mind during verb processing may overwhelm AD patients who may have a material-specific limitation of executive resources. Another factor spotlights the potential role that AD patients' impaired thematic matrix knowledge may play in compromised verb meaning.…”
Section: Difficulty Acquiring the Meaning Of A New Word In Admentioning
confidence: 99%
See 2 more Smart Citations
“…One factor concerns the increased resource demands that may be associated with processing all of the knowledge represented in a verb. Although difficulty with verb confrontation naming and verb-picture matching do not correlate with executive resource deficits in AD White-Devine et al, 1996), we cannot rule out that the need to maintain a rich corpus of semantic, thematic, and grammatical knowledge in mind during verb processing may overwhelm AD patients who may have a material-specific limitation of executive resources. Another factor spotlights the potential role that AD patients' impaired thematic matrix knowledge may play in compromised verb meaning.…”
Section: Difficulty Acquiring the Meaning Of A New Word In Admentioning
confidence: 99%
“…Some work demonstrates that verb meaning is particularly impaired in AD White-Devine et al, 1996;Yi et al, 2006), although others report less impairment for verbs (Fung et al, 2001;Robinson et al, 1999). Several factors may contribute to AD patients' difficulty learning the meaning of a new verb.…”
Section: Difficulty Acquiring the Meaning Of A New Word In Admentioning
confidence: 99%
See 1 more Smart Citation
“…However, verb disorders are not restricted to agrammatic subjects. A number of studies have documented selective verb retrieval impairments in subjects who do not exhibit the symptoms of agrammatism (e.g., Caramazza & Hillis, 1991;Kremin, 1994;Marshall et al, 1996;White-Devine et al, 1996;Jonkers & Bastiaanse, 1998), and in fact, verb disorders have been found across many subtypes of aphasia (Williams & Canter, 1987;Kohn et al, 1989).…”
Section: Introductionmentioning
confidence: 98%
“…Within the past few years, an increasing amount of research has been done on verb retrieval impairments in brain-damaged subjects (McCarthy & Warrington, 1985;Williams & Canter, 1987;Kohn et al, 1989;Zingeser & Berndt, 1990;Damasio & Tranel, 1993;Daniele et al, 1994;Kremin, 1994;Breedin & Martin, 1996;Marshall et al, 1996;White-Devine et al, 1996;Berndt et al, 1997aBerndt et al, , 1997bBreedin et al, 1998;Chen & Bates, 1998;Jonkers & Bastiaanse, 1998;Tranel et al, submitted for publication). In a recent study, we investigated the degree to which various stimulus, lexical, and conceptual factors influenced the ability of 53 brain-damaged subjects to name static pictures of actions with the most appropriate verbs (Kemmerer & Tranel, 2000).…”
Section: Introductionmentioning
confidence: 93%